Scope of Poplar Cultivation - Chandra, J. P. (Indian Forester, 2001)
Natural forest cover of India is declining and timber imports are draining foreign exchange. This is because productivity aspect of forests has been assigned low priority in our policies. To overcome the problem the only answer is plantation forestry which will help in sustainable timber and forest goods production. Poplars were introduced in agroforestry by M/s WIMCO Seedlings Limited almost two decades back. On account of their higher productivity they are conspicuous over agricultural fields in Indo-gangetic plains. At present about 23,000 ha of agricultural land is annually planted with Poplars. Considering total irrigated land of Western Uttar Pradesh, Haryana and Punjab, little has been covered by Poplars. Apart from generating raw material for industries, Poplars are helpful to improve socio-economic status of farmers and generate employment for rural population, mainly on account of their higher productivity and ready market. To avoid monoculture, maintain vigour of clones and pest resistance, thereby maintenance of productivity, regularly new clones of Poplar are needed, for which, breeding programme is a must. M/s WIMCO Seedlings Limited is actively busy in developing new clones of Poplar. Already 9 clones are registered with International Poplar Commission and another 12 clones which are more productive than G-48 are in pipeline. All these 12 clones are expected to increase per unit area wood yield by 150 per cent. At present M/s WIMCO Seedlings Limited is testing 65 clones under multilocational trial and 347 hybrid/half-sib seedlings are ready for release for multilocational field testing. Apart from them, 11,242 seedlings are under study after second stage screening in nursery for field tests. Populus species, which was initially introduced in our country to produce raw material for match industry, has been a gift for veneer industry on account of which large number of plywood units have been established in Northern India. Recently pencil industry has also shown its interest for wood of Poplar and it is expected that compressed wood industry will consume largest portion of Poplar wood in near future.